Association Between Overweight and Central Obesity in Women of Reproductive Age and Overweight in Children Under Five Years of Age - Jaimini Sarkar; Chiradeep Sarkar (Epidemiology, Biostatistics and Public Health)
Objective: Childhood obesity is becoming an emerging public health issue as it is associated with increased morbidity and premature deaths. Determinants like the child’s household characteristics, maternal weight before the preconception stage, and maternal weight in childhood are studied. This study aims to understand the relationship between overweight women of reproductive age and overweight children under the age of five to inform future intervention strategies. Methods: The data for the study were collected from the India’s National Family Health Survey- 5 (NFHS-5). This study is based on publicly available, anonymized secondary data. It has been sub-grouped into urban and rural categories. The percentage of women with high-risk Waist-Hip-Ratio (WHR) and the percentage of overweight women were independent variables whereas the percentage of overweight under-five children was the dependent variable. Spearman rank correlation coefficient, simple linear regression, and multiple linear regression analysis were used to analyze the collected data. Descriptive analysis was done for mean, median, and mode. Results: Study shows the percentage of overweight women has increased by 4.1%, and the percentage of overweight children has increased by 2% during the NFHS5 (2019-21) compared to NFHS4 (2015-16). The Spearman’s rank correlation coefficient (rs) values are 0.4032 for urban, 0.6867 for rural, and 0.5835 for the total population of women with high-risk WHR and overweight children under five years of age whereas the analysis for the percentage of overweight women and percentage of overweight children under five years of age has shown rs=0.389 for rural and rs=0.03893 for total population. Multiple linear regression analysis was done for the total population at a significance level of 0.05 for the independent variables percentage of overweight women, the percentage of women with high risk WHR, and the dependent variable, the percentage of overweight children under five years of age. The results indicated (b0=-3.0448, b1=-0.0202, and b2=0.1397). Simple linear regression of the total population for the independent variable overweight women and dependent variable overweight children under five years of age shows (R=0.0344, Rsquare=0.0012, p-value=0.8421, and b=0.0099) and for the overweight children under five years of age and high-risk WHR women (R=0.5662, Rsquare=0.3205, p-value=0.0003, and b=0.1366). Conclusions: Central obesity or high-risk WHR in women is more common than being overweight. The number of overweight women as well as children under five years is increasing. Central obesity in women shows a moderate positive relation with overweight in children under five years. It shows when the number of women with high-risk WHR increases, there will be an increase in the number of overweight children under five years of age.